2020
DOI: 10.1007/s10570-020-03119-4
|View full text |Cite
|
Sign up to set email alerts
|

In operando monitoring of wood transformation during pretreatment with ionic liquids

Abstract: The conversion of lignocellulosic biomass or wood into chemicals still poses a challenge due to the recalcitrance of this composite-like material consisting of lignin, hemicellulose and cellulose. A very high accessibility of cellulose is reported by a pretreatment with ionic liquids that enables high conversion rates by enzymatic hydrolysis. However, the underlying mechanisms have not yet been monitored in operando nor are they fully understood. We monitored the transformation of wood in ionic liquids using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Furthermore, extraction of cellulose out of industrial paper mill wastewater (Glińska et al 2019) and hemicellulose from a kraft paper pulp (Roselli 2017) using an IL is reported. Viell et al (2020) gave insights into the transformation process in wood treatment with ILs, while Spörl et al (2018) demonstrated a fully recyclable all-cellulose composite, using 1-ethyl-3-methylimidazolium acetate.…”
Section: Ionic Liquids In Combination With Pulp and Papermentioning
confidence: 99%
“…Furthermore, extraction of cellulose out of industrial paper mill wastewater (Glińska et al 2019) and hemicellulose from a kraft paper pulp (Roselli 2017) using an IL is reported. Viell et al (2020) gave insights into the transformation process in wood treatment with ILs, while Spörl et al (2018) demonstrated a fully recyclable all-cellulose composite, using 1-ethyl-3-methylimidazolium acetate.…”
Section: Ionic Liquids In Combination With Pulp and Papermentioning
confidence: 99%
“…Acetic acid was purchased from Armar chemicals (Döttingen, CH). Details on the synthesis can be found in Viell et al [27]. For the XRD measurements, hydrogenous EmimAc (Sigma Aldrich, lot no.…”
Section: Sample Preparationmentioning
confidence: 99%